Effects of combination therapy of statin and N-acetylcysteine for the prevention of contrast–induced nephropathy in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. (1st June 2016) - Park, Soo Hwan; Jeong, Myung Ho; Park, In Hyae; Choi, Jin Soo; Rhee, Jung Ae; Kim, In Soo; Kim, Min Cheol; Cho, Jae Yeong; Sim, Doo Sun; Hong, Young Joon; Park, Hyung Wook; Kim, Ju Han; et al.
Abstract: Background: Acute myocardial infarction (AMI) is a risk factor for contrast-induced nephropathy (CIN). We investigated whether pretreatment with statin, N-acetylcysteine (NAC) and sodium bicarbonate (NaHCO3 ) reduces the risk of CIN. Methods: We conducted a prospective trial and enrolled a total of 334 ST-segment elevation myocardial infarction (STEMI) patients. Patients were divided into four groups: Group I (statin 40 mg), Group II (statin 80 mg), Group III (statin 80 mg plus NAC 1200 mg) and Group IV (regimen of group III plus NaHCO3 154 mEq/L). CIN was defined as ≥ 25% or ≥ 0.5 mg/dL increase in serum creatinine from the baseline within the 72 h after PCI. Results: CIN occurred in 72 (21.6%) patients. The incidence of CIN was the lowest in the group III (14.3%), and multivariate analysis showed the lower incidence of CIN in group III compared to Group I [odds ratio (OR) 0.29, 95% confidence interval (CI) 0.13–0.64, p = 0.002]. Admission hyperglycemia [(AHG) > 198 mg/dL] (OR 2.20, 95% Cl 1.20–3.68, p = 0.011) and the use of intra-aortic balloon pump (IABP) (OR 4.20, 95% CI 1.38–12.78, p = 0.016) were independent predictors for CIN. The CIN (OR 9.00, 95% CI 1.30–62.06, p = 0.026) was an independent predictor for in-hospital mortality. Conclusions: Combination of high-dose statin plus NAC was associated with lower incidence of CIN in patients with STEMI who underwent primary PCI compared to statin only.